UJI AKTIVITAS ANTIOKSIDAN PADA SERBUK SARI INSTAN DAUN PUDING HITAM (Graptophyllum Pictum L. Griff) MENGGUNAKAN METODE DPPH - Herlina; Anisa Agustina; Tri Yanuarto; Elly Mulyani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Instant beverages are an innovation in herbal products that are practical, easy to serve, and have a longer shelf life compared to liquid preparations, making them widely developed as health drinks. Black pudding leaves (Graptophyllum pictum L. Griff) are known to contain flavonoid compounds that act as antioxidants and have the potential to be processed into instant beverages. This study aimed to evaluate the antioxidant activity of instant pollen powder from black pudding leaves using the DPPH method and to determine the IC₅₀ value as an indicator of antioxidant strength. The preparations were made in three formulations with concentrations of 20%, 30%, and 50%. The results showed that all formulations exhibited very strong antioxidant activity, with IC₅₀ values of 16.827 ppm (F1), 16.375 ppm (F2), and 7.713 ppm (F3). All IC₅₀ values were within the very active category (IC₅₀ < 50 ppm). These findings indicate that instant pollen powder of black pudding leaves has great potential to be developed as a natural antioxidant source in the form of a functional herbal drink that is not only easy to consume but also beneficial in helping protect the body against free radical damage.